MODIN SEBAGAI PATRONASE PERKAWINAN DI KOTA SEMARANG, SEBUAH TINJAUAN ANTROPOLOGI BUDAYA - I Nyoman Yoga Segara (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
This paper discusses how the structure of culture continues to work to produce the construction of meaning for what has happened behind a marriage event. In a social fact, a marriage often involves many things, including the actor and agent of the culture behind it. In Semarang, Central Java, modinhas become a spotlight because of its role and status in the community has resulted in the high cost of marriage which goes beyond the specified condition. It can be read clearly from the results of research conducted at two locations, namely the Religious Affairs Office (KUA) in West Semarang and Mijen districts. The key question of this research is explored by qualitative method, ie interview, observation, and documentary study. The research argues that the application of regulation that has not been maximized, some constraints, low public response, and the presence of weaknesses in the regulation itself, has been used by actors ofmodin to continue to build relationship as patronage to the people who need them. The patron-client relationship cannot be easily eliminated as relation of modin-bride/groom has been culturally and historicallylongstanding and mutually interdependent.